The Role of Micronutrient Supplementation in the Management of Hashimoto’s Thyroiditis: A Review of Current Evidence and Potential Mechanisms of Action - Michalska, Sara; Makuch, Rafał; Gała, Kamil; Lenard, Paweł; Kucharski, Adam; Pilarski, Konrad; Dewicka, Martyna; Wawrzyniak, Alicja Maria; Chrościcka, Alicja; Czajka, Andrzej (Quality in Sport, 2024)
Introduction and objective: Hashimoto’s thyroiditis (HT), the most prevalent autoimmune disorder and a primary cause of hypothyroidism globally, leads to thyroid gland damage through lymphocyte infiltration. Pharmacological treatment of HT involves the use of levothyroxine, which in most cases must be taken for life. However, supplementation with micronutrients is often overlooked. Several studies have examined the impact of substances such as selenium, zinc, vitamin B12, and vitamin D on the course of Hashimoto’s disease. Review methods: Review and summary of research studies available in open-source format on Google Scholar, PubMed. Abbreviated description of the state of knowledge: Supplementation with selenium, zinc, vitamin D, and B12 shows potential benefits for patients with Hashimoto’s disease. Summary: Regular monitoring and tailored supplementation of selenium, zinc, vitamin D, and vitamin B12 can enhance overall health and disease management. Therefore, it is worth considering the supplementation of these micronutrients in the daily routine of patients with Hashimoto’s thyroiditis. However, it should be noted that these supplements do not constitute a treatment for Hashimoto’s disease and their effect cannot replace the intake of levothyroxine.